Pemaknaan Takut Akan Tuhan Dalam Kehidupan Anak-Anak Generasi Alpha: Penerapan Reader Response Criticisem Amsal 1:7 - Ramida Br. Padang; Herdiana Boru Hombing; Bernhardt Siburian (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The purpose of this study was to determine the meaning of the fear of God in Proverbs 1:7. The research method in writing this scientific paper is a qualitative method, namely with the Reader Response Criticism (PRC) approach. Based on the results of the author's interview that has been conducted with 10 Alpha Generation Children at GKPPD Kuta Kerangan who became informants for research in the field, it can be seen that in the initial discussion there were 4 out of 10 informants, 40% of whom the author interviewed had read the text, and 2 out of 10 informants, 20% had read the text for the first time. There are 4 out of 10 informants, 40% of whom have never read the text. Then the author also asks if there is an interesting word in the text of Proverbs 1:7? 7 out of 10 informants responded by saying an interesting word for fear and 3 out of 10 said an interesting word in Proverbs 1:7 for fool. The author can conclude that there are 4 out of 10 informants, 40% who are quite diligent in worshiping and participating in church activities (PA), and 6 out of 10 informants, 60% who are less active in church and worship activities. But in the study, although 4 out of 10 informants who were fairly diligent in worship, it was not determined how he responded to the text correctly, so that 7 out of 10 informants, 70%, only 3 out of 10 informants, 30% responded correctly to the text. The Alpha generation children in Aceh Singkil can be said to not know exactly how to fear God in their lives. As said by Risnawaty Sinulingga (2010) and Matthew Henry (2013) that the fear of God in question is everything that must be known, that God must be respected, served, and worshiped, thus the meaning of fearing God is part of a good character that avoids evil, and obeys His commandments.